VERP and brain imaging for identifying levels of visual dorsal and ventral stream function in typical and preterm infants. - Braddick, O; Atkinson, J; Wattam-Bell, J (2011)
Visual development is a key area for understanding and assessing early brain development. Different levels in the hierarchy of visual processing, from the initial response to flashes of light, through selective responses to contour orientation and motion in primary visual cortex (V1), to global processing in extrastriate of large-scale patterns of form and motion, can each be assessed using stimuli designed to isolate specific neural activity in visual event-related potentials (VERPs). This approach has been used to reveal the sequence of emergence of different visual cortical functions in the first 6 months of typical human development, and to provide early indicators of anomalies in brain development. Delayed or absent onset of orientation-reversal (OR-)VERPs, as a measure of cortical development, has been shown to be a sensitive indicator of perinatal brain damage in both term-born and prematurely born infants. Direction-reversal (DR-)VERPs appear a few weeks later than OR-VERPs in typical development, and are further delayed in even healthy children born preterm, reflecting possible early vulnerability of the motion (dorsal stream) system. High-density recordings of responses to global motion and global form patterns show that these extrastriate systems are typically functional by 5 months of age, but the topography of the activity distributions shows that the brain systems underlying these responses are radically reorganized between infancy and adulthood. In prematurely born infants whose structural brain MRI was evaluated at birth, the onset of the response is absent or delayed in those with severe brain injury, while in those with mild/moderate brain injury the response is present but its spatial organization is further from the adult pattern than those in controls. These findings are related to the development of distinct networks of brain areas in the dorsal and ventral cortical streams, and the apparent vulnerability of the dorsal-stream network in a wide range of both genetic and acquired developmental disorders.